Calibration of Local Magnitude Scales for Use in Seismic Monitoring. - Murphy, J. R.; Marshall, M. E.; Barker, B. W.; Bennett, T. J.; Grant, L. T. (1995)
In situations where cavity decoupling of underground nuclear explosions is a plausible evasion scenario, comprehensive seismic monitoring of any eventual CTBT will require the routine identification of many small seismic events with magnitudes in the range 2.0 < m sub b < 3.5. However, since such events are not expected to be detected teleseismically, their magnitudes will have to be estimated from regional recordings using seismic phases and frequency bands which are different from those employed in the teleseismic m sub b scale which is generally used to specify monitoring capability. Therefore, it is necessary to establish the m sub b equivalences of any selected regional magnitude measures in order to estimate the expected detection statistics and thresholds of proposed CTBT seismic monitoring networks. In the investigations summarized in this report, this has been accomplished through analyses of synthetic data obtained by theoretically scaling observed regional seismic data recorded in Scandinavia and Central Asia from various tamped nuclear tests to obtain estimates of the corresponding seismic signals to be expected from small cavity decoupled nuclear tests at those same source locations. (MM)